Pyrazolo[1,5-a][1,3,5]triazines(5-Aza-9-deazapurines): Synthesis and Biological Activity - Dolzhenko, Anton; Dolzhenko, A.; Chui, W. (The Japan Institute of Heterocyclic Chemistry, 2008)
The present review gives an account on the synthetic routes to pyrazolo[1,5-a][1,3,5]triazine system, which is an isostere of purine, and polyfused systems bearing this heterocyclic core. Data concerning biological activity of compounds with pyrazolo[1,5-a][1,3,5]triazine skeleton are also discussed.